Effects of Adlerian joint parent-child counseling on children's disruptive behavior - Ugay, Herminia Alcala (Animo Repository, 1990)
This study examines extent of changes brought about by an Adlerian joint parent-child counseling after the counseling process.The study used an idiographic design (n=1) using 10 cases, 9 of which are replication studies. All cases used joint parent-child counseling as treatment modality. The pre-test and post-test treatment of the data was gathered from the following instruments: Child Rearing Practices Scale, Behavior Checklist, CPQ Intelligence, Excitability, Guilt Proneness and Ergic Tension Scales. Likewise, oral feedback were gathered from significant others.For those who completed the counseling process, results of the study point out the following to be true:1. Joint parent-child counseling brought positive changes in the client.2. Child Rearing Practices Scale revealed changes in scores from 4 to 5-6 which tend to make them democratic rather than authoritarian.3. Behavior Checklist showed disruptive behavior change from scale score of 2 to 4 indicating a change of disruptive behavior occurrence from often to rarely .4. Children's Personality Questionnaire revealed that counselees A, B, D and J reduced their excitability scores from sten of 7-9 to sten scores of 5-6 which lessened their excitability. The guilt proneness scale showed a reduction of 1 scale score for 6 to 5. There was a decrease of their guilt proneness. The ergic tension scale scores were sustained from pre-assessment to post-assessment. These were all within normal limits. There was neither a decrease nor decrease. 5. Oral feedback reported changes in their disruptive behavior. Likewise, feelings of being rejected were changed to feelings of being cared for and listened to. Further, feedback from significant others also reported changes of disruptive behaviors from occurring sometimes to rarely .6. Child clients realized that disruptive behaviors were caused by mistaken beliefs and conclusions on their own subjective perceptions on parents' interaction with them.7. Child-parent clients gave commitment to change their dysfunctional behavior by attending sessions and doing tasks required in between sessions.Tentative conclusions from the findings of the study were:1. Counselees have to set own goals and commit time and effort to benefit from the treatment.2. Changes in disruptive behavior were brought about by correcting mistaken beliefs held by counselees.3. Modification of the type of parent-client interaction brought about changes in both feelings and behavior.4. Changes of feelings and beliefs occurred as therapy proceeded even before manifestation of goal of behavior change.5. Parents' child rearing practices to some extent, negatively or positively influenced childrens' behavior.6. Joint parent-child counseling to some extent proved effective in bringing changes in occurrence frequency of disruptive behavior, in the well-being of counselee in terms of excitability, quilt proneness and ergic tension.7. Psycho-education to some extent bring about changes in child rearing practices of parents.